2011
DOI: 10.1016/j.jval.2011.08.1394
|View full text |Cite
|
Sign up to set email alerts
|

PRS7 Efficacy and Safety of Sildenafil Above 60 mg Daily in Pulmonary Arterial Hypertension Treatment - a Systematic Literature Review

Abstract: To assess efficacy and safety of dornase alfa in the treatment of cystic fibrosis (CF) in children and adults. METHODS: Systematic review of Medline, Em-Base, CENTRAL and clinicaltrials.gov databases was conducted. The references from relevant articles and abstracts from conferences were also examined to identify any additional studies. Each full-text article was critically appraised with use of the Jadad Scale. Clinical practice and CF treatment procedures in Poland were consulted with clinical experts. Place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…In this study, we focused on 20 mg/TID, and included participants who were mainly idiopathic PAH, as well as CTD and CHD related PAH. The results on 6MWD, mean PAP, dyspnoea score, level of BNP were similar to those identi ed in other systematic reviews [16,[21][22][39][40][41][42] . As an important indicator for severity evaluation and prognosis [43] , previous studies have shown that there was a signi cant improvement in WHO functional class favouring sildena l when comparing to placebo [16] .…”
Section: Discussionsupporting
confidence: 88%
“…In this study, we focused on 20 mg/TID, and included participants who were mainly idiopathic PAH, as well as CTD and CHD related PAH. The results on 6MWD, mean PAP, dyspnoea score, level of BNP were similar to those identi ed in other systematic reviews [16,[21][22][39][40][41][42] . As an important indicator for severity evaluation and prognosis [43] , previous studies have shown that there was a signi cant improvement in WHO functional class favouring sildena l when comparing to placebo [16] .…”
Section: Discussionsupporting
confidence: 88%
“…In this study, we focused on 20 mg/TID, and included participants who were mainly idiopathic PAH, as well as CTD and CHD-related PAH. The results of 6MWD, mean PAP, dyspnoea score, and level of BNP were similar to those identified in other systematic reviews (16,21,22,(43)(44)(45)(46). As an important indicator for severity evaluation and prognosis (47), previous studies have shown that there is a significant improvement in WHO functional class favouring sildenafil comparing to the placebo (16).…”
Section: Discussionsupporting
confidence: 86%
“…Among these, both the FDA and EMA recommended that sildenafil be orally administered at a dose of 20 mg/TID. Although increasing evidence has suggested that sildenafil therapy is beneficial (21,22,(43)(44)(45)(46), the dose varies greatly. A Cochrane systematic review published in 2019 indicated that sildenafil has a better therapeutic effect, with a lower incidence of adverse events compared to the placebo (16).…”
Section: Discussionmentioning
confidence: 99%